Tafs?r a?-?uruq fi at-Ta’l?m; Kontekstualisasi Ayat-Ayat al-Qur’an Perspektif Tarbaw? Berdimensi Metode Pembelajaran - Saeful Bahri (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat (LP3M) Institut Agama Islam Bakti Negara (IBN) Tegal, 2019)
The contextualization of al-Qur'an through the perspective of tarbaw? gives an understanding of the content of the learning method. For example, al-M?idah [05]: 67 in the context of education can be understood as the delivery of learning by the lecture method. Furthermore, the letter an-Nahl [16]: 125 has an articulation in the content of the discussion method with nuances of tenderness. Meanwhile, the method of contemplation is reflected in the letter Ibr?h?m [14]: 24-25. Interaction and visiting certain places in the letter Y?s?f [12]: 109 contains the method of field trips. The retrieval of rah ibrah through past events and the stories of previous generations as reflected in Y?s?f's letter [12]: 111 can be contextualized as the delivery of messages by the story method.